Performance optimization and injury prevention in floorball: a systematic literature review of biomechanical, physiological, and technological evidence - Ardo Okilanda; Ifdil Ifdil; Rudyanto Rudyanto; M. Arie Desman (Indonesian Institute For Counseling, Education and Therapy, 2026)
Floorball is a fast, multidirectional indoor team sport in which performance and injury risk emerge from interacting tactical, biomechanical, neuromuscular, physiological, and monitoring factors. This systematic review synthesised evidence from 2005–2026 across three linked domains: performance determinants, injury risk and prevention, and technologies for monitoring and prediction. PRISMA 2020 guided the review, and Scopus was used as the primary information source because it spans sport science, biomechanics, and engineering literature. The search identified 63 records; 30 full texts were assessed and 10 empirical studies were included: five prospective/longitudinal, three cross-sectional, one observational match-analysis, and one intervention-plus-modelling study. Thematic synthesis identified three evidence clusters. Performance was associated with tactical decision-making, shooting coordination, reactive lower-limb strength, directional-speed symmetry, and load-sensitive psychophysiological state. Injury evidence centred on ACL-related landing and neuromuscular-control factors, but no single screen consistently predicted future injury. Emerging technologies included wearables, velocity-based training, machine learning, and automated tracking, with modest individual-level predictive validity. The review therefore proposes a hypothesis-generating monitoring-informed framework that links performance and injury domains while requiring larger prospective cohorts, external validation, stronger female- and youth-specific evidence, and replication across databases.